Geopolymer Material with Coconut Husk Additive as Heavy Metal Absorbances for Malacca River Water - Pillay, Gokkul; Zaidi Embong (Enhanced Knowledge in Sciences and Technology, 2024)
Concern is raised on the escalating issue of heavy metal pollution in the Malacca River by proposing an eco-friendly solution through the synthesis of geopolymer composites enriched with coconut husk. Employing SEM/EDX and ICPMS techniques, we evaluated the porosity and heavy metal absorption capacities of these composites. The research objectives aimed to identify an optimal geopolymer pellet for purifying contaminated river water. Water samples from the Malacca River were initially analysed using ICPMS to establish baseline heavy metal concentrations. Subsequently, geopolymer samples with varied compositions were immersed in the contaminated water, and SEM/EDX assessed their porosity, while ICPMS analysed heavy metal content before and after exposure. Findings revealed distinct variations in heavy metal absorption capacities among different geopolymer formulations, with promising results in reducing contamination levels. This research contributes valuable insights into sustainable water purification materials, specifically addressing heavy metal pollution in river systems. The successful synthesis of a geopolymer material, enhanced with coconut husk, underscores its potential as an eco-friendly remedy for mitigating heavy metal contamination. The identified MK-65%, POFA-35% with 3%-CH geopolymer pellet holds promise for water remediation, emphasizing the significance increase of porosity contribute to higher removal efficiency.